Community composition and spatial energetics of mesopelagic fishes and squids in the eastern Bering Sea as influenced by habitat variables. (April 2022) - Sinclair, E.H.; Pelland, N.A.; Johnson, D.S.
Abstract: Micronekton of the mesopelagic zone (200 m–1000 m depth) play a central role in most aspects of global marine ecology linking epipelagic and deep scattering layers as planktivores, carnivores and principal prey to both shallow diving and deep living apex predators. Yet, despite this critical role and conspicuous presence, little is known regarding most aspects of mesopelagic community ecology, including habitat associations at sub-basin spatial scales. Here we address several aspects of these data deficiencies in the eastern Bering Sea mesopelagic – a highly productive subarctic marine ecosystem home to multiple protected predator species and large commercial fisheries. Through 41 midwater trawls conducted at 250 m, 500 m and 1000 m depths during May of 1999 and 2000, and a series of generalized linear models and cluster analyses, we describe the influence of remotely sensed oceanographic habitat variables on the diel distribution, relative abundance and community composition of 30 species of mesopelagic fish and squid in 3 contrasting study areas. We then project the total energy available to predators at depth and across the eastern Bering Sea Basin based on the identified habitat constraints. Fishes from the families Bathylagidae and Myctophidae, and squids from the Gonatidae dominated the 72 species catch biomass (n = 225, 000, 2, 100 kg). The six most abundant species were equally divided between each of the three dominant families and are also the most highly represented mesopelagic species in eastern Bering Sea pelagic predator diets. Their association with surface habitat variables describe a complex and multifaceted relationship between physical/biological predictors and the total mesopelagic energy field during the spring bloom period in this ecosystem. Leuroglossus schmidti, Bathylagus pacificus, Stenobrachius leucopsaurus, S. nannochir, Gonatopsis borealis and Eogonatus tinro contrast in the suite of physical and biological variables that they respond to, and also in the character of their response. Although L. schmidti is of moderate caloric value, it expressed the greatest overall energy signature at all depths due to its overwhelming biomass, and response to the presence of specific, variable habitat conditions across extensive portions of the study area. Interannual variability in habitat variables forecasted a pronounced redistribution of dominant species and thereby total mesopelagic energy content – providing a potential mechanism for shifts in central-place predator habitat use, energy expenditure, and diet. The known relevance of mesopelagic species as prey and the energetic potential for apex predators foraging in the Basin illustrates a cautionary narrative regarding unregulated harvest of biota from this poorly understood and critically important oceanic zone. Highlights: Community composition of mesopelagic fish and cephalopod species dielly at depth in the eastern Bering Sea basin. Relationships between physical and biological habitat variables and mesopelagic species distributions. Dynamic distribution of mesopelagic species and subsequent energetic potential to predators at depth.